When Kamay Met Hill: Organisational Ethics in Practice - Batten, Jonathan A. (Journal of business ethics, 2018)
The Kamay and Hill insider trading conviction in Australia highlights many of the issues and problems involved in the prevention, detection and prosecution of insider trading. The case uniquely highlights how ethical behaviour is instilled at home, in school and in society, and the need for ethical responsibility at the personal and organisational level to complement legal rules and enforcement. We use the Kamay and Hill case to explore the reasons behind the failure of the traditional top-down approach to insider trading prevention, where institutional ethical codes of conduct largely reflect and rely upon national rules, norms, and regulation. We propose a bottom-up approach to ensure that individual and organisational behaviour is ethical, where emphasis is not on compliance but on a set of core ethical values that allow individual and corporate expression. It is our strong belief that compliance cannot replace ethics.